European Association of Urology-American Society of Clinical Oncology Collaborative Guideline on Penile Cancer: 2023 Update - Brouwer, Oscar R.; Albersen, Maarten; Parnham, Arie; Protzel, Chris; Pettaway, Curtis A.; Ayres, Benjamin; Antunes-Lopes, Tiago; Barreto, Lenka; Campi, Riccardo; Crook, Juanita; Fernández-Pello, Sergio; Greco, Isabella; et al. (European urology, 2023)
Penile cancer is a rare disease but its incidence is increasing and there are many unmet needs to address. This collaborative guideline provides updated information on the diagnosis and treatment of penile cancer. The lack of controlled trials and large series means that the levels of evidence and grades of recommendation are low in comparison to those for more common diseases. Referral to centres of expertise is recommended. Penile cancer is a rare disease but has a significant impact on quality of life. Its incidence is increasing, so it is important to include new and relevant evidence in clinical practice guidelines. To provide a collaborative guideline that offers worldwide physician and patient guidance for the management of penile cancer. Comprehensive literature searches were performed for each section topic. In addition, three systematic reviews were conducted. Levels of evidence were assessed, and a strength rating for each recommendation was assigned according to the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) methodology. Penile cancer is a rare disease but its global incidence is increasing. Human papillomavirus (HPV) is the main risk factor for penile cancer and pathology should include an assessment of HPV status. The main aim of primary tumour treatment is complete tumour eradication, which has to be balanced against optimal organ preservation without compromising oncological control. Early detection and treatment of lymph node (LN) metastasis is the main determinant of survival. Surgical LN staging with sentinel node biopsy is recommended for patients with a high-risk (≥pT1b) tumour with cN0 status. While (inguinal) LN dissection remains the standard for node-positive disease, multimodal treatment is needed in patients with advanced disease. Owing to a lack of controlled trials and large series, the levels of evidence and grades of recommendation are low in comparison to those for more common diseases. This collaborative penile cancer guideline provides updated information on the diagnosis and treatment of penile cancer for use in clinical practice. Organ-preserving surgery should be offered for treatment of the primary tumour when feasible. Adequate and timely LN management remains a challenge, especially in advanced disease stages. Referral to centres of expertise is recommended. Penile cancer is a rare disease that significantly impacts quality of life. While the disease can be cured in most cases without lymph node involvement, management of advanced disease remains challenging. Many unmet needs and unanswered questions remain, underlining the importance of research collaborations and centralisation of penile cancer services.